Control mechanisms for the integration of teaching and service in the Pró-Saúde nursing programme - Selma Regina de Andrade; Astrid Eggert Boehs; Carlos Gabriel Eggert Boehs; Pollyana Plautz Gorris
Objective: To characterize and analyze the control mechanisms of institutional relations for the integration of health education and services linked to the Pro-Saúde programme, according to the professors and nurses of health centres in Florianópolis.Method: A qualitative approach based on a single case study. Sixteen semi-structured interviews were conducted in the second semester of 2012 at eight health centres where nursing students carry out practical activities and internships in primary health care. The data were subjected to content analysis with the comparison of responses from both segments.Results: Three categories were created: Characterization of control mechanisms; Influences of control mechanisms; and, Suggestions for the improvement of control mechanisms for the integration of teaching and services.Conclusion: A greater understanding of the control mechanisms for the integration of teaching and services proportionally leads to better management of inter-organizational cooperation and the subsequent improvement of the care provided to users.